2022
DOI: 10.1126/sciadv.abq6842
|View full text |Cite
|
Sign up to set email alerts
|

Ice-nucleating agents in sea spray aerosol identified and quantified with a holistic multimodal freezing model

Abstract: Sea spray aerosol (SSA) is a widely recognized important source of ice-nucleating particles (INPs) in the atmosphere. However, composition-specific identification, nucleation processes, and ice nucleation rates of SSA-INPs have not been well constrained. Microspectroscopic characterization of ambient and laboratory-generated SSA confirms that water-borne exudates from planktonic microorganisms composed of a mixture of proteinaceous and polysaccharidic compounds act as ice-nucleating agents (INAs). These data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 80 publications
0
12
0
Order By: Relevance
“…This closure approach will be applied also within the planned MOSAiC studies (to be presented in follow-up articles). In the first step, the ice-nucleation rate J het is computed as a function of SSA specific parameters k = 26.6132 and b = -3.9346 (Alpert et al, 2022) and for a given ice-nucleation temperature and ice supersaturation S ICE . The product of s dry × J het × ∆t then yields n INP .…”
Section: Arctic Aerosol Of Continental Originmentioning
confidence: 99%
See 2 more Smart Citations
“…This closure approach will be applied also within the planned MOSAiC studies (to be presented in follow-up articles). In the first step, the ice-nucleation rate J het is computed as a function of SSA specific parameters k = 26.6132 and b = -3.9346 (Alpert et al, 2022) and for a given ice-nucleation temperature and ice supersaturation S ICE . The product of s dry × J het × ∆t then yields n INP .…”
Section: Arctic Aerosol Of Continental Originmentioning
confidence: 99%
“…These recent findings point to a strong role of biogenic INPs in Arctic ice nucleating processes in summer. Alpert et al (2022) present an INP parameterization to estimate INPs concentrations for sea spray aerosol, applicable to lidar observations. While soil dust particles most likely dominate ice nucleation in the lower troposphere (<2.5 km) in winter, when cloud top temperatures in mixed-phase clouds are usually far below −15 to −20°C, local INPs of biogenic origin seem to control ice nucleation in the boundary layer in summer when cloud top temperatures in mixed-phase clouds with typical top heights below 2.5 km are usually > −15°C (Griesche et al, 2021;Creamean et al, 2022).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Support for this consideration comes from studies that analyzed ambient particle populations and INPs micro-spectroscopically on an individual particle level (Knopf et al, 2018;Laskin et al, 2016). Those studies find that the INPs are chemically and morphologically not significantly different than particles that do not act as INPs (Alpert et al, 2022;China et al, 2017;Hiranuma et al, 2013;Knopf et al, 2014Knopf et al, , 2018Lata et al, 2021), consistent with a stochastic freezing process (i.e., one particle out of many same ones induced freezing). Consequently, in the ABIFM case, for each modeling time step, the number of activatable INPs is reassessed taking the entire activatable aerosol population into account (since special INPs are not assigned).…”
Section: Conceptual Approachmentioning
confidence: 99%
“…For example, mineral dust particles with large emission rates of up to 5000 Tg yr –1 are recognized as the most important INP type because of their generally effective ice nucleation ability. Previous studies have found that dust particles activate as ice crystals at temperatures above −15 °C in the immersion mode . Additionally, biological aerosols including bacteria, pollen, viruses, fungi, and phytoplankton can also act as effective INPs with freezing temperatures ranging from −3 °C for bacteria to below −38 °C for marine aerosols. Furthermore, many studies have shown the pervasive presence of ammonium sulfate and sulfuric acid particles in the upper troposphere. These particles exhibit homogeneous freezing temperatures below −38 °C, playing a significant role in the formation of cirrus clouds. …”
Section: Introductionmentioning
confidence: 99%